The importance of an active case detection (Acd) programme for malaria among migrants from malaria endemic countries: The greek experience in a receptive and vulnerable area - Tseroni, Maria; Georgitsou, Maria; Baka, Agoritsa; Pinaka, Ourania; Pervanidou, Danai; Tsironi, Maria; Bleta, Panagiota; Charvalakou, Maria; Psinaki, Ioanna; Dionysopoulou, Martha; Legaki, Antonia; Vakali, Annita; et al. (My University, 2020)
Greecehasbeenmalaria-freesince1974. InOctober2011,followinganoutbreakof36locally acquired malaria (LAM) cases in Evrotas Municipality, a Pro-Active Case Detection (PACD) program for malaria was implemented among migrants from malaria-endemic countries, to support early diagnosis and treatment of cases. We evaluated the PACD program for the years 2012–2017 using indicatorssuchasthenumberoflocallyacquiredcases,thedetectionrate/sensitivityandthetimeliness of diagnosis and treatment. We visited each migrant home every 7–15 days to screen migrants for malaria symptoms, performing Rapid Diagnostic Tests (RDTs) and blood smears on symptomatic patients. We estimated: (i) the number of malaria cases detected by the PACD, divided by the total number of reported malaria cases during the same period among the same population; (ii) the time betweenonsetofsymptoms,diagnosisandinitiationoftreatment. Thetotalnumberofmigrantswho were screened for malaria symptoms for the years 2012–2017 was 5057 with 84,169 fever screenings conducted, while 2288 RDTs and 1736 blood smears were performed. During the same period, 53 imported P. vivax malaria cases were detected, while incidence of malaria among migrants was estimated at 1.8% annually. Ten and one LAM cases were also reportedin 2012 and 2015, respectively. Sensitivity of PACD ranged from 86% to 100%; median timeliness between onset of symptoms and diagnosis decreased from 72 h in 2012 to 12 h in 2017 (83% decrease), while timeliness betweendiagnosis and treatment initiation was 0 h. The implementation of PACD could be considered an eﬀective prevention and response tool against malaria re-introduction.
Keywords: Active case detection; Greece; Malaria; Migrants; Plasmodium vivax